2022
DOI: 10.3389/fcvm.2022.979461
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of lipoproteins, membranes, and extracellular vesicles in understanding C-reactive protein biochemical structure and biological activities

Abstract: Early purification protocols for C-reactive protein (CRP) often involved co-isolation of lipoproteins, primarily very low-density lipoproteins (VLDLs). The interaction with lipid particles was initially attributed to CRP’s calcium-dependent binding affinity for its primary ligand—phosphocholine—the predominant hydrophilic head group expressed on phospholipids of most lipoprotein particles. Later, CRP was shown to additionally express binding affinity for apolipoprotein B (apo B), a predominant apolipoprotein o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 111 publications
1
4
0
Order By: Relevance
“…In our cohort, we found that mCRP, in addition to the above-described distribution pattern, often was scattered diffusely as small granules embedded within the stroma, unrelated to any particular cell type. Consistent with previous studies delineating the precise ligands for mCRP (5), this morphological pattern could indicate possible crosstalk between mCRP and components of the ECM. Given the putative pro-inflammatory properties of mCRP, such direct interactions could potentially contribute to excessive stromal formation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our cohort, we found that mCRP, in addition to the above-described distribution pattern, often was scattered diffusely as small granules embedded within the stroma, unrelated to any particular cell type. Consistent with previous studies delineating the precise ligands for mCRP (5), this morphological pattern could indicate possible crosstalk between mCRP and components of the ECM. Given the putative pro-inflammatory properties of mCRP, such direct interactions could potentially contribute to excessive stromal formation.…”
Section: Discussionsupporting
confidence: 90%
“…Recently, evidence has been advanced showing that CRP exists in different structural isoforms with distinct biological activities (4). The circulating CRP isoform is a highly soluble pentameric molecule (pCRP) composed of 5 identical globular subunits arranged in a ringshaped structure (5). Each subunit contains a calcium dependent binding site enabling interaction with phosphocholine (PC), a major component of plasma membranes, defined as the primary ligand for pCRP.…”
Section: Introductionmentioning
confidence: 99%
“…Adhesion was negated in the presence of an anti-CD18 mAb, correlating with the previous finding that pCRP with anti-P-selectin and anti-CD18 promoted complete blockade of adhesion between neutrophils and monocytes (See Neutrophil Discussion) (65). mCRP (1-30 mg/mL), specifically, also increased monocyte chemoattractant protein-1 (MCP-1) and IL-8 secretion, key mediators of leukocyte recruitment, as well as neutrophilendothelial cell adhesion via the expression of ICAM-1, VCAM-1 and E-selectin (25). To observe the similar effects with nCRP preparations, a 6x longer incubation was required, implicating that pentameric dissociation had occurred.…”
Section: Mcrp Upregulates Endothelial Cell Adhesionmentioning
confidence: 95%
“…Hydrophobic interactions with lipid rafts are predicted to compensate for non-receptor binding. Evidence for lipid-promoted conformational dynamics is exhibited by the association of mCRP with extracellular lipid vesicles ( 26 ). Activated leukocytes slough membrane-bound CRP, which enters circulation as extracellular vesicles upon cleavage.…”
Section: Posited Pcrp → Mcrp Conformational Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation